The Dark Side of the Mushroom Spring Microbial Mat: Life in the Shadow of Chlorophototrophs. II. Metabolic Functions of Abundant Community Members Predicted from Metagenomic Analyses - Thiel, Vera; Hügler, Michael; Ward, David M.; Bryant, Donald A. (Frontiers in Microbiology, 2017)
Abstract. Microbial mat communities in the effluent channels of Octopus and Mushroom Springs within the Lower Geyser Basin of Yellowstone National Park have been extensively characterized. Previous studies have focused on the chlorophototrophic organisms of the phyla Cyanobacteria and Chloroflexi. However, the diversity and metabolic functions of the other portion of the community in the microoxic/anoxic region of the mat, are poorly understood. We recently described the diverse but extremely uneven microbial assemblage in the undermat of Mushroom Spring based on 16S rRNA amplicon sequences, which was dominated by Roseiflexus members, filamentous anoxygenic chlorophototrophs. We analyzed the assembled metagenome of the orange-colored undermat portion of the community of Mushroom Spring mats and here discuss the genomic potential and metabolic functions of the major members. This part of the community was found to be a mixture of photo- and chemotrophic organisms, which use bicarbonate as well as organic carbon sources derived from different cell components and fermentation products. The presence of rhodopsin genes in many taxa strengthens the hypothesis that light energy is of major importance. Evidence for the usage of all four bacterial carbon fixation pathways was found in the metagenome. Nitrogen fixation appears to be limited to Synechococcus spp. in the upper mat layer and Thermodesulfovibrio sp. in the undermat, and nitrate/nitrite metabolism was limited. A closed sulfur cycle is indicated by biological sulfate reduction combined with the presence of genes for sulfide oxidation mainly by phototrophs. Finally, a variety of undermat microorganisms have genes for hydrogen production and consumption, which leads to the observed diel hydrogen concentration patterns.